Comprehensive recovery of zinc, iron and copper from copper slag by co-roasting with SO2–O2 - Da-wei Wang; Yan-jie Liang; Zhang Lin; Cong Peng; Bing Peng (Journal of Materials Research and Technology, 2022)
In this study, a novel method to recover copper, zinc and iron from copper slag by SO2–O2 roasting-leaching-magnetic separation was proposed. The effect of roasting experiment conditions were roasting temperature of 900 °C, holding time of 120 min, and φSO2 (The volume fraction of SO2 in the mixed gas of SO2 and O2) of 90%. Under the leaching conditions of leaching temperature 80 °C, leaching time 1 h, liquid–solid ratio 14:1, and pH 7, 91.03% of copper and 85.04% of zinc can be recycled respectively. The iron in the leaching residue can be enriched and recovered by magnetic separation at a magnetic field strength of 3000 Gs for 40 min. The iron recovery rate is 85.88% with 53.86% of the iron grade in the concentrate.